Desenvolvimento de um modelo experimental de transtorno bipolar bifásico em ratos - Barroso, Poliana Noronha (2019)
Bipolar disorder (BD) is a serious and disabling psychiatric condition that affects 2% of the world's population. Clinically, it is characterized by a cyclic variation of mood phases, between mania (or euphoria) and depression. Due to its clinical complexity, the development of an animal model that effectively reproduces BD remains a challenge for researchers in this field. In scientific literature, the use of animal models to mimic BD has focused on separate phases of the disorder, and few studies have validated strategies that include both manic and depressive phases in one experimental trajectory. The development of an animal model involves the validation of three criteria: a) face validity, which refers to how adequately the model induces the signs and symptoms of the modeled disease; b) the construct validity, which analyzes the ability of a model to reproduce the etiopathological process and the pathophysiological mechanisms of the disease and its biological alterations; and c) the predictive (pharmacological) validity, in which we assess the model's response to therapeutic approaches to the disease, if it can be reversed or attenuated with treatment, and if we can predict the effects of the intervention in human subjects. In this study, we developed a model of BD induced by repeated administration of amphetamine in rats. For this, male Wistar rats were treated with amphetamine in two different protocols, to induce manic and depressive symptoms. In the manic phenotype, the animals received 7 days of amphetamine treatment (2.0 mg/kg). On the seventh day, the rats underwent behavioral testing and were sacrificed for removal of brain areas. For the depressive phenotype, the animals received 7 days of amphetamine treatment (2.0 mg/kg), which was suspended from the 8th to the 21st day. After this period, the rats were equally evaluated and sacrificed. Additionally, a group of lithium-treated animals was included in each protocol, to assess the reversal potential of model-induced changes. The results showed that the Phase Mania protocol promoted manic-type behavior in animals. In the Phase Depression protocol, the Sucrose Preference test promoted depressive-type behavior, which is highly relevant in the assessment of depression. Further research will be needed to consolidate this two-phase model in the study of Bipolar Disorder.